Zinc and Lead Leaching from Sphalerite–Galena Concentrate Using Deep Eutectic Solvents Based on Choline Chloride: Effect of Roasting and Iodine as Oxidizing Agent - Katherine Moreno; Ximena Díaz; Diana Endara; Fernando Sánchez; Carlos F. Aragón-Tobar (Molecules, 2024)
The traditional metallurgical routes for producing lead and zinc from primary sources have a significant environmental footprint. Thus, using less pollutant solvents, such as deep eutectic solvents (DESs), would offer a greener solution in metal extraction. This study explores the use of three DESs based on choline chloride (ChCl) (1:2 ChCl–urea, 1:2 ChCl–ethylene glycol, and 1:2 ChCl–glycerol) for recovering Zn and Pb from a sphalerite–galena concentrate of the mining region in Ecuador. Leaching tests of the concentrate (untreated and roasted at 600 °C) in each DES were conducted (30 °C—24 h). The effect of adding iodine as an oxidizing agent was also evaluated. Recoveries of 2% (Zn) and 14% (Pb) were reported when leaching the untreated concentrate with DES. These recovery values increased to 11% (Zn) and 99% (Pb) after adding iodine during the leaching of the untreated concentrate. Roasting had a similar effect on leaching, increasing the recovery values of Zn (75%) and Pb (90%). Combining roasting as a pretreatment and iodine as an oxidizing agent produced higher Zn recoveries (99%) and Pb (99%). These results were compared to recoveries in acid leaching (H2SO4 and HNO3), revealing the potential of DESs as an alternative for metal recovery from primary sources.